Haploidentical bone marrow transplantation in patients with relapsed or refractory severe aplastic anaemia in the USA (BMT CTN 1502): a multicentre, single-arm, phase 2 trial. Issue 9 (September 2022) - DeZern, Amy E; Eapen, Mary; Wu, Juan; Talano, Julie-An; Solh, Melhem; Dávila Saldaña, Blachy J; Karanes, Chatchada; Horwitz, Mitchell E; Mallhi, Kanwaldeep; Arai, Sally; Farhadfar, Nosha; Hexner, Elizabeth; et al.
Summary: Background: Relapsed severe aplastic anaemia is a marrow failure disorder with high morbidity and mortality. It is often treated with bone marrow transplantation at relapse post-immunosuppressive therapy, but under-represented minorities often cannot find a suitably matched donor. This study aimed to understand the 1-year overall survival in patients with relapsed or refractory severe aplastic anaemia after haploidentical bone marrow transplantation. Methods: We report the outcomes of BMT CTN 1502, a single-arm, phase 2 clinical trial done at academic bone marrow transplantation centres in the USA. Included patients were children and adults (75 years or younger) with severe aplastic anaemia that was refractory (fulfilment of severe aplastic anaemia disease criteria at least 3 months after initial immunosuppressive therapy) or relapsed (initial improvement of cytopenias after first-line immunosuppressive therapy but then a later return to fulfilment of severe aplastic anaemia disease criteria), adequate performance status (Eastern Cooperative Oncology Group score 0 or 1, Karnofsky or Lansky score ≥60%), and the presence of an eligible related haploidentical donor. The regimen used reduced-intensity conditioning (rabbit anti-thymocyte globulin 4·5 mg/kg in total, cyclophosphamide 14·5 mg/kg daily for 2 days, fludarabine 30 mg/m 2 daily for 5 days, total body irradiation 200 cGy in a single fraction), related HLA-haploidentical donors, and post-transplantation cyclophosphamide-based graft-versus-host disease (GVHD) prophylaxis. Additionally, for GVHD prophylaxis, mycophenolate mofetil was given orally at a dose of 15 mg/kg three times a day up to 1 g three times a day (maximum dose 3000 mg per day) from day 5 to day 35, and tacrolimus was given orally or intravenously from day 5 to day 180 as per institutional standards to maintain a serum concentration of 10–15 ng/mL. The primary endpoint was overall survival 1 year after bone marrow transplantation. All patients treated per protocol were analysed. This study is complete and is registered with ClinicalTrials.gov, NCT02918292 . Findings: Between May 1, 2017, and Aug 30, 2020, 32 patients with relapsed or refractory severe aplastic anaemia were enrolled from 14 centres, and 31 underwent bone marrow transplantation. The median age was 24·9 years (IQR 10·4–51·3), and median follow-up was 24·3 months (IQR 12·1–29·2). Of the 31 patients who received a transplant, 19 (61%) were male and 12 (39%) female. 13 (42%) patients were site-reported as non-White, and 19 (61%) were from under-represented racial and ethnic groups; there were four (13%) patients who were Asian, seven (23%) Black, one (3%) Hawaiian/Pacific Islander, and one (3%) more than one race, with seven (23%) patients reporting Hispanic ethnicity. 24 (77%) of 31 patients were alive with engraftment at 1 year, and one (3%) patient alive with autologous recovery. The 1-year overall survival was 81% (95% CI 62–91). The most common grade 3–5 adverse events (seen in seven or more patients) included seven (23%) patients with abnormal liver tests, 15 (48%) patients with cardiovascular changes (including sinus tachycardia, heart failure, pericarditis), ten (32%) patients with gastrointestinal issues, seven (23%) patients with nutritional disorders, and eight (26%) patients with respiratory disorders. Six (19%) deaths, due to disease and unsuccessful bone marrow transplantation, were reported after transplantation. Interpretation: Haploidentical bone marrow transplantation using this approach results in excellent overall survival with minimal GVHD in patients who have not responded to immunosuppressive therapy, and can expand access to bone marrow transplantation across all populations. In clinical practice, this could now be considered a standard approach for salvage treatment of severe aplastic anaemia. Attention to obtaining high cell doses (>2·5 × 10 8 nucleated marrow cells per kg of recipient ideal bodyweight) from bone marrow harvests is crucial to the success of this approach. Funding: US National Heart, Lung, and Blood Institute and US National Cancer Institute.